Soil texture, soil organic carbon and total nitrogen contents from samples of the Mt. Kilimanjaro - Adrian Guetlein (PANGAEA, 2020)
Physicochemical soil properties were derived from each soil core(N = 60) of 5 times replicated 12 Kilimanjaro ecosystems. Soil pH was measured from 10 g air-dried soil samples dissolved in 25 ml 0.01 molar CaCl2 solution with a SenTix 61 electronic pH-meter (WTW GmbH, Weilheim, Germany). Soil organic carbon (SOC) and total nitrogen (Ntot) contents were determined using an elemental analyzer(Elementar Analysensysteme, Hanau, Germany; measured by University of Hohenheim) according to DIN ISO 13878, 10694, and 15178. Soil texture (<2 mm) was analyzed by laboratory facilities of the University of Hohenheim, Germany. Sample material was pretreated with HCl and H2O2, respectively, to disturb CaCO3 and organic matter before texture distribution was analyzed. Sand was sieved with 630, 200, and 63 lm mesh sizes. Then the silt and clay contents were determined with the classical pipette method sedimentation. Bulk density (BD) was calculated from undisturbed soil cores (100 cm^3), which were collected at the in situ sites (N = 60) at 0–5 cm soil depth and subsequently oven dried (72 hr at 105°C). The stone fraction was measured from the same samples by means of the water displacement of stones >2 mm.